Mathematical modeling of the onion drying process: Kinetic and Thermodynamic Parameters - Giménez-López, Bruno; Ronceros, Cristhian; Quispe, Alejandro; Cusi, Rosalio; Giménez-Medina, Manuel; Cuba, Carmen (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
The dehydration processes of onions are governed by a series of kinetic and thermodynamic parameters that, when controlled, facilitate the identification of a mathematical model that will improve the efficiency and quality of the drying process in terms of reducing production costs, environmental sustainability, and the development of innovative products. In this study, various mathematical models were validated to accurately describe the drying process, and from them, the kinetic and thermodynamic parameters governing the dehydration processes were determined. For the experimental development, onions grown in the Ica region of Peru were peeled, cut into pieces, and dehydrated (60, 70, and 80 ºC), and five mathematical models were applied to model the drying kinetics of the process. The Midilli model was the best fit for the experimental curves. Increasing the temperature reduced the enthalpy and increased the entropy, Gibbs free energy, and effective diffusion coefficient in both varieties of onions. Determining the drying kinetics has been essential for establishing operating conditions by understanding how temperature, relative humidity, and other parameters affect the moisture removal rate, allowing for the design of optimal equipment and predicting product behavior during the drying process.